2022
DOI: 10.3390/diagnostics12020543
|View full text |Cite
|
Sign up to set email alerts
|

Strain Imaging for the Early Detection of Cardiac Remodeling and Dysfunction in Primary Aldosteronism

Abstract: Speckle tracking echocardiography is a novel technique to quantify cardiac function and deformation. It has been applied in a series of cardiovascular diseases for the evaluation of early cardiac impairment. We recently used this technique to investigate cardiac structure and function in patients with primary aldosteronism. Cardiac damage usually occurs earlier in patients with primary aldosteronism than those with primary hypertension, probably because aldosterone hypersecretion is more commonly observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 118 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…This might be linked to the influence on the right ventricular systolic function via the helical muscle bundle, interventricular septum, and pericardium shared by the two ventricles, which increases with the LVMI ( 16 ). In addition, the SBP might affect the right ventricular free wall longitudinal strain as follows: when the blood pressure is elevated, various vasoactive substances mediated by activating the renin-angiotensin-aldosterone system could induce fibrosis and degeneration of the pulmonary vascular wall and intima, further affecting the right ventricular systolic function ( 29 , 30 ). Soylu et al ( 31 ) found a remarkably higher plasma aldosterone level in patients with concentric hypertrophy compared with patients with normal geometric and concentric remodeling, which might lead to different right ventricular myocardial mechanics for different left ventricular geometric patterns.…”
Section: Discussionmentioning
confidence: 99%
“…This might be linked to the influence on the right ventricular systolic function via the helical muscle bundle, interventricular septum, and pericardium shared by the two ventricles, which increases with the LVMI ( 16 ). In addition, the SBP might affect the right ventricular free wall longitudinal strain as follows: when the blood pressure is elevated, various vasoactive substances mediated by activating the renin-angiotensin-aldosterone system could induce fibrosis and degeneration of the pulmonary vascular wall and intima, further affecting the right ventricular systolic function ( 29 , 30 ). Soylu et al ( 31 ) found a remarkably higher plasma aldosterone level in patients with concentric hypertrophy compared with patients with normal geometric and concentric remodeling, which might lead to different right ventricular myocardial mechanics for different left ventricular geometric patterns.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of plasma aldosterone‐to‐renin ratio for primary aldosteronism screen, the prevalence of primary aldosteronism is high, being 6%–8% in patients with hypertension in primary care 35 , 36 and up to 15% in patients with resistant hypertension 37 or patients with both hypertension and diabetes mellitus. 38 Patients with primary aldosteronism have more severe target organ damage 39 , 40 , 41 , 42 , 43 and higher risks of stroke, atrial fibrillation, acute myocardial infarction and heart failure than patients with primary hypertension matched for blood pressure. 44 The current endocrine 13 and hypertension 9 , 10 , 11 guidelines strongly advocate screening for primary aldosteronism in various groups of hypertensive patients, such as those with moderate or severe hypertension, treatment‐resistant hypertension, spontaneous or diuretic‐induced hypokalemia, adrenal incidentaloma, atrial fibrillation, obstructive sleep apnea syndrome, or a family history of early (< 40 years of age) onset hypertension or cerebrovascular accident, and the first‐degree relatives of patients with primary aldosteronism.…”
Section: Blood Pressure Control In Primary Aldosteronism Screenmentioning
confidence: 99%